2021
DOI: 10.1073/pnas.2020680118
|View full text |Cite
|
Sign up to set email alerts
|

Tungsten-182 evidence for an ancient kimberlite source

Abstract: Globally distributed kimberlites with broadly chondritic initial 143Nd-176Hf isotopic systematics may be derived from a chemically homogenous, relatively primitive mantle source that remained isolated from the convecting mantle for much of the Earth’s history. To assess whether this putative reservoir may have preserved remnants of an early Earth process, we report 182W/184W and 142Nd/144Nd data for “primitive” kimberlites from 10 localities worldwide, ranging in age from 1,153 to 89 Ma. Most are characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…While this process cannot be completely ruled out, it is not favored here because surface-derived, high-δ 13 C oxidized carbon can be efficiently recycled into the upper mantle as shown by some diamonds ( 83 ) and mantle xenoliths ( 84 ). Conversely, the transition zone provides an effective thermal barrier to the subduction of oxidized carbon into the lower mantle ( 43 ), from where most kimberlites are probably sourced ( 20 , 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…While this process cannot be completely ruled out, it is not favored here because surface-derived, high-δ 13 C oxidized carbon can be efficiently recycled into the upper mantle as shown by some diamonds ( 83 ) and mantle xenoliths ( 84 ). Conversely, the transition zone provides an effective thermal barrier to the subduction of oxidized carbon into the lower mantle ( 43 ), from where most kimberlites are probably sourced ( 20 , 23 , 24 ).…”
Section: Methodsmentioning
confidence: 99%
“…The genetic link between kimberlites and deep mantle plumes is reinforced by the distribution of some kimberlite fields along age-progressive corridors corresponding to the continental portions of hot spot tracks ( 21 ). Furthermore, the relatively homogeneous Nd and Hf isotope composition and the occurrence of negative 182 W anomalies in kimberlites older than ~200 Ma requires tapping of a deep source largely isolated from mantle convection and associated recycled crustal components ( 22 , 23 ), and hence probably located in the lowermost mantle ( 24 ). This is supported by the entrainment of superdeep diamonds, which contain inclusions of minerals stable in the mantle transition zone and lower mantle [e.g., ringwoodite ( 25 ) and CaSi-perovskite ( 26 )], and the He and Ne isotope systematics of olivine in some kimberlites, which require deep-mantle plume contributions ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this process cannot be completely ruled out, it is not favored here because surface-derived, high- 13 C oxidized carbon can be efficiently recycled into the upper mantle as shown by some diamonds (83) and mantle xenoliths (84). Conversely, the transition zone provides an effective thermal barrier to the subduction of oxidized carbon into the lower mantle (43), from where most kimberlites are probably sourced (20,23,24).…”
Section: Carbon Isotopes Versus Sr-nd-hf Isotopesmentioning
confidence: 99%
“…The genetic link between kimberlites and deep mantle plumes is reinforced by the distribution of some kimberlite fields along ageprogressive corridors corresponding to the continental portions of hot spot tracks (21). Furthermore, the relatively homogeneous Nd and Hf isotope composition and the occurrence of negative 182 W anomalies in kimberlites older than ~200 Ma requires tapping of a deep source largely isolated from mantle convection and associated recycled crustal components (22,23), and hence probably located in the lowermost mantle (24). This is supported by the entrainment of superdeep diamonds, which contain inclusions of minerals stable in the mantle transition zone and lower mantle [e.g., ringwoodite (25) and CaSi-perovskite (26)], and the He and Ne isotope systematics of olivine in some kimberlites, which require deep-mantle plume contributions (27).…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the exact depth of kimberlite genesis below the lithosphere‐asthenosphere boundary (LAB), the source region(s) is likely to represent a mix of multiple components. For example, some studies have indicated the presence of “ancient”, “refractory” or “primordial” components in the source of these rocks (e.g., Giuliani et al., 2021; Nakanishi et al., 2021; Tappe, Budde, et al., 2020; Woodhead et al., 2019), as well as the incorporation of “subducted/recycled” and “enriched” material into the kimberlite source region (e.g., Giuliani et al., 2022; Nowell et al., 2004; Tappe et al., 2013; Tovey et al., 2021; Woodhead et al., 2019).…”
Section: Introductionmentioning
confidence: 99%